Validation of factor structure of the neurodevelopmental parent report for outcome monitoring in down syndrome: confirmatory factor analysis - Baumer, Nicole T.; Pawlowski, Katherine G.; Zhang, Bo; Sideridis, Georgios (Frontiers in Psychiatry, 2024)
The Neurodevelopmental Parent Report for Outcome Monitoring (ND-PROM), initially developed to monitor developmental and behavioral functions in children within autism spectrum disorder (ASD), assesses symptoms across a wide range of domains relevant in DS. Psychometric properties of ND-PROM were assessed in 385 individuals with DS and 52 with a combined diagnosis of DS and ASD (DS+ASD), whose caregivers completed the ND-PROM questionnaire for a clinical visit in a specialized Down syndrome program at a tertiary pediatric hospital. Confirmatory factor analysis was conducted to evaluate the internal structure validity of the ND-PROM. Measurement invariance was assessed, with a comparison group of 246 individuals with ASD, and latent mean differences between the DS and ASD-only groups, as well as the combined DS+ASD groups, were assessed. Findings support the existence of the 12 clinically-derived factors in the DS population: Expressive Language, Receptive Language, Adaptive skills / Toileting, Social Emotional Understanding, Social Interaction, Independent Play, Sensory Processes, Challenging Behaviors, Impulse/ADHD, and Mental Health. Differences in response patterns of development and behaviors were observed between those with DS and those with ASD, including those with DS having higher abilities in nonverbal communication, social emotional understanding, and social interaction, and fewer restricted and repetitive behaviors and interests, impulsivity or ADHD symptoms, and mental health concerns compared to those with ASD. Individuals in the DS+ASD group had more difficulties with expressive and receptive language, nonverbal and social communication, social interaction, independent play, and adaptive skills than either the DS-only group or the ASD-only groups. The ND-PROM has a desirable factor structure and is a valid and clinically useful tool that captures a range of distinct and independent areas of developmental and behavioral functioning in DS, for individuals with and without an ASD diagnosis.